A study of the effect of motor structural components on harmonic noise - Weijie Zhang; Hao Li (Scientific Reports)
Abstract This paper introduces the characteristics of the harmonic noise of the outdoor unit of air conditioner, analyzes the change of the noise sound pressure level and the corresponding spectral characteristics of the outdoor unit when the harmonic noise is generated, and researches the influence of the core structural components of the outdoor unit such as the motor structure, bracket structure, etc., on the spectral characteristics of the harmonic noise. It is found that with the increase of harmonic content in the power supply, the harmonic noise with 200 Hz frequency characteristics is generated, and the noise peak at a fixed frequency of 200 Hz increases gradually with the increase of harmonic content, and the larger the harmonic content of the power supply, the higher the noise peak. Combined with the analysis of the vibration characteristics of a single motor, whether it is a single motor (no load) or the whole outdoor unit (with load) operation, the iron shell motor in the front and rear direction of the vibration amplitude is higher, while the plastic motor in the three directions of the vibration vibration amplitude of the vibration is relatively uniform, the main reason for this is determined by the motor’s own magnetic field characteristics. The resonance of the motor bracket may be due to the fact that the solid frequency of the motor bracket is equal or similar to the motor excitation frequency. Optimize the modal frequency of the motor bracket to avoid the motor excitation frequency, and its 14th-order modal frequency actively avoids the motor excitation frequency, so that there is no resonance phenomenon in the outdoor unit.